Defending Surveillance Sensor Networks Against Data-Injection Attacks via Trusted Nodes - R. López-Valcarce; Daniel Romero (European Signal Processing Conference (EUSIPCO), 2017)
By injecting false data through compromised sensors, an adversary can drive the probability of detection in a sensor network-based spatial field surveillance system to arbitrarily low values. As a countermeasure, a small subset of sensors may be secured. Leveraging the theory of Matched Subspace Detection, we propose and evaluate several detectors that add robustness to attacks when such trusted nodes are available. Our results reveal the performance-security tradeoff of these schemes and can be used to determine the number of trusted nodes required for a given performance target.
Keywords: winter; wsn